ENOX2-based early detection (ONCOblot) of asbestos-induced malignant mesothelioma 4–10 years in advance of clinical symptoms. Issue 1 (December 2016) - Morré, D.; Hostetler, Brandon; Taggart, David; Morré, Dorothy; Musk, A.; Robinson, Bruce; Creaney, Jenette
Abstract Background Malignant mesothelioma is an aggressive, almost uniformly fatal tumor, caused primarily by exposure to asbestos. In this study, serum presence of mesothelioma-specific protein transcript variants of ecto-nicotinamide adenine dinucleotide oxidase disulfide-thiol exchanger 2 (ENOX2), a recently identified marker of malignancy, were investigated using the ONCOblot tissue of origin cancer detection test. Methods Sequential serum samples collected from asbestos-exposed individuals prior to the development of frank mesothelioma were assayed for ENOX2 presence by 2-D gel immunoblot analysis to determine how long in advance of clinical symptoms mesothelioma-specific ENOX2 transcript variants could be detected. Results Two mesothelioma-specific ENOX2 protein transcript variants were detected in the serum of asbestos-exposed individuals 4–10 years prior to clinical diagnosis of malignant mesothelioma (average 6.2 years). Either one or both ENOX2 protein transcript variants indicative of malignant mesothelioma were absent in 14 of 15 subjects diagnosed with benign pleural plaques either with or without accompanying asbestosis. Conclusions In a population of asbestos-exposed subjects who eventually developed malignant mesothelioma, ENOX2 protein transcript variants characteristic of malignant mesothelioma were present in serum 4–10 years in advance of clinical symptoms. As with all biomarker studies, these observations require validation in a larger, independent cohort of patients and should include prospective as well as retrospective sampling.